PUBLIC SPEAKING IN ISLAMIC HIGH SCHOOL: PRACTICAL STEPS ON ISLAMIC CIVILIZATION TOPICS - Rafika Rabba Farah; Puji Sumarsono; Alimin Adi Waloyo (Universitas Islam Negeri Mataram, Indonesia, 2019)
Abstract The tenet of being able to speak English in public sphere as a global life skill has now been a driving force for many Indonesians to learn English since early age. Not only in educational sector, public speaking skill is also in high demand for nowadays’ context—industrial marketplace era. Yet, in many situations, teachers fail to support students with the necessary skills to perform public speaking. As English is still a foreign language in Indonesia, assigning students to perform public speaking without proper training leads into fear or anxiety. However, a practical training into what the best practices of public speaking should be undertaken by educators. Moreover, Indonesia as the biggest Muslim country has many Islamic schools around. For Islamic high school students, Islamic-based material is the content that likely becomes the discourse of the school curriculum. To preach Islam in a global level, English can open up ways to this. Thus, the notion of infusing Islamic-based content in public speaking classroom is necessary. Implementing this, a training on Public Speaking with Islamic-based materials were conducted in Madrasah Aliyah Muhammadiyah 1 Malang Indonesia. The study results in highlighting several practical steps for Public Speaking with Islamic Civilization content. Procedures will highlight on experienced-based learning and some techniques to support a local-based atmosphere. In so doing, this present study suggests that Islamic Civilization content can be used as a supporting material for students learning in Islamic school context. Therefore, it is recommended that teachers in Islamic school can design the curriculum that underlies Islamic elements.